Virtual lesion clinic – Evaluation of a teledermatology triage system for referrals for suspected melanoma. (27th December 2021) - Teague, Rebecca; Wang, Mark; Wen, Daniel; Sunderland, Michael; Rolfe, Gill; Oakley, Amanda M M; Rademaker, Marius; Martin, Richard
Abstract: Introduction: The Virtual Lesion Clinic (VLC) of Waitematā District Health Board (WDHB) improves melanoma assessment and treatment using teledermatology. The VLC is reserved for pigmented lesions referred as suspected melanoma from primary care but indeterminate at the initial triage. Objectives: To assess the efficacy of the VLC diagnosis of melanoma. Methods: A retrospective audit of suspected melanoma referrals (1 January 2012 to 31 December 2016) was conducted. Lesions were referred to the VLC if diagnostic uncertainty remained at the initial triage. VLC patients attended MoleMap imaging centres, a dermatologist reviewed history and images remotely and suggested a diagnosis and management plan. Post VLC provisional diagnosis of melanoma, all lesions subsequently excised were reviewed. A positive predictive value (PPV) was calculated using concordance between VLC diagnosis of melanoma and histopathological diagnosis of melanoma. Number needed to excise (NNE) for melanoma was derived, as well as an invasive to in‐situ melanoma ratio (IM:MIS) and false negative rate (FNR). Results: The VLC received 1874 referrals for 3546 lesions during the 5‐year study period. Six hundred and seventy‐nine lesions were recommended excision/biopsy or specialist face‐to‐face assessment, and 504 lesions were subsequently excised. The PPV was 62%, NNE 1.62 and IM:MIS 0.76 for lesions suspected to be melanoma at VLC assessment. The VLC had a melanoma‐specific FNR of 7%. Conclusions: The VLC is effective in early diagnosis of melanoma with a high positive predictive value, low number needed to excise and low false negative rate amongst lesions referred as suspected melanoma.